THE ROLE OF THE MADRASAH HEAD AS THE INITIATOR OF HUMAN RESOURCES ORGANIZING - Sholehatun, Sholehatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to investigate the efforts of the madrasah head in organizing the human resources of MI Miftahul Jannah Wangkal Gading Probolinggo. The research method used a qualitative approach of the case study type. Data were collected through the processes of observation, interviews with the madrasah head, the Curriculum Vice Principal (Waka Kurikulum), the madrasah committee, one of the madrasah teachers, and documentation. The data were analyzed through the processes of data condensation, data presentation, and drawing conclusions. Triangulation of sources was used as a tool to measure the data validity. The research results indicate that the three organizational processes conducted by the madrasah head of MI Miftahul Jannah Wangkal Gading Probolinggo as an initiator demonstrate systematic and mechanical managerial processes by adjusting the capabilities of the human resources available. These processes include structuring (clear organizational structure), assembling resources (organizing the human resources available according to the organization's needs), and staffing (placing human resources according to their abilities and qualifications). Certainly, the head of MI Miftahul Jannah Wangkal Gading Probolinggo is capable of being an initiator in the hierarchical order as a step in organizing high-quality organizational human resources